1993
DOI: 10.1152/ajprenal.1993.265.6.f875
|View full text |Cite
|
Sign up to set email alerts
|

H-K-ATPase in distal renal tubular acidosis: urinary tract obstruction, lithium, and amiloride

Abstract: In previous studies we suggested that urinary tract obstruction and chronic administration of lithium or amiloride were models of "voltage-dependent" distal renal tubular acidosis (DRTA). Subsequently, differences among these three models suggested that the pathogenesis was far more complex than we originally proposed. A recent study showed that H-adenosinetriphosphatase (H-ATPase) activity was decreased in all three experimental models. In the current experiments we examined the effect of 24-h unilateral uret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…In the present study, we observed maintained targeting of ␣-, ␤-, and ␥-ENaC in BUO and of ␣-and ␤-ENaC in obstructed kidneys from UUO rats, which in part may be caused by increased aldosterone levels as has been demonstrated in previous studies in rats with urinary tract obstruction (6,31,37). This finding is consistent with previous observations on AQP2 in response to obstruction, where protein expression and labeling intensity was reduced after BUO but with maintained apical targeting of AQP2 (9).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, we observed maintained targeting of ␣-, ␤-, and ␥-ENaC in BUO and of ␣-and ␤-ENaC in obstructed kidneys from UUO rats, which in part may be caused by increased aldosterone levels as has been demonstrated in previous studies in rats with urinary tract obstruction (6,31,37). This finding is consistent with previous observations on AQP2 in response to obstruction, where protein expression and labeling intensity was reduced after BUO but with maintained apical targeting of AQP2 (9).…”
Section: Discussionsupporting
confidence: 87%
“…Of note, with reference to our findings, is the potential role played by the renin-angiotensin-aldosterone (RAA) system, which has a considerableinvolvement in the pathophysiology of UUO, as highlighted by the upregulation of plasma aldosterone levels secondary to 24 hours of UUO in rats [26]. Elsewhere, in pigs, it has been shown that there is an enhanced ipsilateral generation of intrarenal angiotensin II during UUO [27].…”
Section: Discussionmentioning
confidence: 72%
“…39,[46][47][48] Also, the in vivo activity of ENaC, the lithium entry site of principal cells, has been reported to be functionally paired with CA activity, because CA inhibition by acetazolamide reduced the intracellular pH and ENaC activity in sweat duct cells and colon. 49,50 However, mpkCCD cells may not fully represent principal cells, and because intercalated cells express abundant levels of CA2, -4, 52,53 it has been suggested that acidosis-induced proliferation of a-intercalated cells may contribute to Li-NDI. 16 It is unlikely, however, that attenuation of Li-NDI in our mice is caused by direct action of acetazolamide on a-intercalated cells or collecting duct remodeling for several reasons.…”
Section: Discussionmentioning
confidence: 99%